2016
DOI: 10.1126/science.aac5681
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for histone H2B deubiquitination by the SAGA DUB module

Abstract: Monoubiquitinated histone H2B plays multiple roles in transcription activation. H2B is deubiquitinated by the Spt-Ada-Gcn5 acetyltransferase (SAGA) coactivator, which contains a four-protein subcomplex known as the deubiquitinating (DUB) module. The crystal structure of the Ubp8/Sgf11/Sus1/Sgf73 DUB module bound to a ubiquitinated nucleosome reveals that the DUB module primarily contacts H2A/H2B, with an arginine cluster on the Sgf11 zinc finger domain docking on the conserved H2A/H2B acidic patch. The Ubp8 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
285
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 228 publications
(313 citation statements)
references
References 48 publications
9
285
1
9
Order By: Relevance
“…A previous report by another group demonstrated that the ZnF-Sgf11 domain of ATXN7L3 is essential for DUB activity toward H2Bub1 in vitro (6). The ZnFSgf11 domain is also required for ATXN7L3 binding to nucleosomal DNA (11), and the crystal structure of the DUB module reveals that an arginine cluster in the ZnF-Sgf11 domain directly interacts with ubiquitinated nucleosomes and H2A/H2B heterodimer (12). Therefore, the absence of this domain in ATXN7L3B indicates that it is unlikely to interact with histones, consistent with our findings that the ATXN7L3B-DUB module cannot efficiently deubiquitinate histones in vitro and that ATXN7L3B is largely localized to the cytoplasm in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report by another group demonstrated that the ZnF-Sgf11 domain of ATXN7L3 is essential for DUB activity toward H2Bub1 in vitro (6). The ZnFSgf11 domain is also required for ATXN7L3 binding to nucleosomal DNA (11), and the crystal structure of the DUB module reveals that an arginine cluster in the ZnF-Sgf11 domain directly interacts with ubiquitinated nucleosomes and H2A/H2B heterodimer (12). Therefore, the absence of this domain in ATXN7L3B indicates that it is unlikely to interact with histones, consistent with our findings that the ATXN7L3B-DUB module cannot efficiently deubiquitinate histones in vitro and that ATXN7L3B is largely localized to the cytoplasm in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The ZnF-Sgf11 domain of ATXN7L3 is essential for DUB activity toward H2Bub1 in vitro (6). The ZnF-Sgf11 domain is required for ATXN7L3 binding to nucleosomal DNA (11), and the crystal structure of the DUB module reveals that an arginine cluster in the ZnF-Sgf11 domain directly interacts with ubiquitinated nucleosomes and H2A/H2B heterodimer (12).…”
mentioning
confidence: 99%
“…In this line, Schulze and colleagues demonstrated that Ubp8 deubiquitinates H2BK123ub 1 at H3K4me 3 -marked regions (Schulze et al, 2011). Indeed, recent studies have revealed that the DUBm subunit, Sgf11 ZnF domain targets the nucleosome core particle (NPC) acidic patch (Morgan et al, 2016 …”
Section: Mog1 Co-purifies With Components Of the Transcription Machinerymentioning
confidence: 86%
“…Recent research has proposed that the DUBm principally contacts H2A/H2B by the basic Sgf11-ZnF domain. In addition, these researchers also found that the DUBm deubiquitinates from either intact or disassembled nucleosomes suggesting that it is able to act at diverse points as RNA Pol II transcribes through chromatin (Morgan et al, 2016). In addition to the organization of the DUBm components for Ubp8 activation, some studies have reported that DUBm needs to be assembled into SAGA complex for its correct function.…”
Section: Dubm Function and Structurementioning
confidence: 99%
See 1 more Smart Citation